2008
DOI: 10.1007/s00405-008-0765-y
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the validity of tympanometry compared to myringotomy performed under a nitrous oxide-free general anaesthetic

Abstract: To assess the validity of tympanometry as a test for the presence of middle ear effusion using a 'gold-standard' of myringotomy performed after a nitrous oxide-free general anaesthetic, we performed a prospective validity study comparing tympanometry traces obtained immediately pre-operatively from patients undergoing grommet insertion, with the otomicroscopic findings at myringotomy. Nitrous oxide was omitted from the anaesthetic gaseous mixture as it has been reported to displace middle ear effusions. One hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Fishpool et al [16], for example, have shown that tympanometry has a 27% false negative rate (unable to detect cases with true OME) in children with confirmed OME using myringotomy and a 16% false positive rate (incorrectly identifying cases as having OME); these findings have been confirmed by several investigators [17,18]. This is in agreement with tympanometric findings reported previously for older children with DS [19].…”
supporting
confidence: 89%
“…Fishpool et al [16], for example, have shown that tympanometry has a 27% false negative rate (unable to detect cases with true OME) in children with confirmed OME using myringotomy and a 16% false positive rate (incorrectly identifying cases as having OME); these findings have been confirmed by several investigators [17,18]. This is in agreement with tympanometric findings reported previously for older children with DS [19].…”
supporting
confidence: 89%
“…In children, diagnosis and screening for SOM involves assessment of middle ear mechanical function. Diagnostic tests for SOM include otoscopy, pneumatic otoscopy and impedance audiometry …”
Section: Introductionmentioning
confidence: 99%
“…In the diagnosis of middle ear effusion, the performance of a fl at tympanogram (type B in the Jerger classifi cation, Jerger, 1970) has been shown to be good (Sassen et al, 1994;Fishpool et al, 2009). However, as TPP is added to diagnostic criteria, the performance of tympanometry becomes poor.…”
Section: Discussionmentioning
confidence: 99%